The Visibility of Airborne Volcanic Ash from the Flight Deck of an Aircraft – The Effect of Clouds in the Field of View - Sauer , Daniel; Gasteiger, Josef; Emde, Claudia; Buras, Robert; Mayer, Bernhard; Weinzierl, Bernadett (AIP Conference Proceedings, 2013)
In April 2010, the volcanic ash cloud from the Eyjafjalla volcano in Iceland strongly impacted aviation in Europe. Several other incidents in the past have shown that volcanic ash can have severe consequences on aviation. One operational necessity is, therefore, to determine whether a pilot has the means to avoid flying through potentially dangerous volcanic ash just by visual observation of the sky from the cockpit of an aircraft. Here we investigate how clouds affect the visibility of a volcanic ash aerosol layer for an observer in the cockpit of an aircraft using a 3D Monte Carlo radiative transfer model MYSTIC. This study builds on the results of a previous study on the visibility of airborne volcanic ash in Weinzierl et al. (2012) where we considered the cloud-free case. With clouds, the discernibility of ash layers is substantially reduced. Even layers with comparably high mass concentrations of 2 mg m−3 might not be visible for uninformed observers.